2022
DOI: 10.3389/fphar.2021.777395
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic Analysis Reveals the Protection Mechanism of GLP-1 Analogue Dulaglutide on High-Fat Diet-Induced Chronic Kidney Disease in Mice

Abstract: Many clinical studies have suggested that glucagon-like peptide-1 receptor agonists (GLP-1RAs) have renoprotective properties by ameliorating albuminuria and increasing glomerular filtration rate in patients with type 2 diabetes mellitus (T2DM) and chronic kidney disease (CKD) by lowering ectopic lipid accumulation in the kidney. However, the mechanism of GLP-1RAs was hitherto unknown. Here, we conducted an unbiased lipidomic analysis using ultra-high-performance liquid chromatography/electrospray ionization-q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…SGLT2Is, and apparently also GLP1RAs, offer kidney protection, and both, especially GLP1RAs, induce weight loss, 34 with visceral and ectopic fat loss 16,36–38 . Reductions in kidney‐PF with these agents have recently been detected in several rodent studies, 39–44 as well as one human study 30 . In the latter, treatment with a GLP1RA (liraglutide), relative to placebo, for 26 weeks significantly reduced kidney‐PF, assessed with MRS, among 17 participants with T2D (mean eGFR: 96 mL/min/1.73m 2 ; median UACR: 16 mg/g), even although baseline median kidney‐PF was only around 0.2% 30 …”
Section: Discussionmentioning
confidence: 99%
“…SGLT2Is, and apparently also GLP1RAs, offer kidney protection, and both, especially GLP1RAs, induce weight loss, 34 with visceral and ectopic fat loss 16,36–38 . Reductions in kidney‐PF with these agents have recently been detected in several rodent studies, 39–44 as well as one human study 30 . In the latter, treatment with a GLP1RA (liraglutide), relative to placebo, for 26 weeks significantly reduced kidney‐PF, assessed with MRS, among 17 participants with T2D (mean eGFR: 96 mL/min/1.73m 2 ; median UACR: 16 mg/g), even although baseline median kidney‐PF was only around 0.2% 30 …”
Section: Discussionmentioning
confidence: 99%
“…Due to its inhibitory effect on protein kinase C (PKC)-β and concurrent amplificatory action on protein kinase A (PKA), Beinaglutide reduced NADPH oxidases activation, leading to a diminished ROS and glycation end-product accumulation in renal glomeruli and tubules [ 140 , 141 ]. The antioxidant effect of GLP-1 is also supported by the enhancement in oxidative stress metabolites, such as NAD+ and adenosine, and cardiolipin essential for mitochondrial metabolism after Semaglutide and Dulaglutide treatment, respectively [ 142 , 143 ]. Reduction in ROS correlated with the lowered urinary albumin/creatinine ratio and alleviated progression in glomerulopathy.…”
Section: Metabolic Therapeutics: Unveiling Mechanisms For Ckd Managementmentioning
confidence: 99%
“…In parallel, Yeung et al reported that the protective effect of dulaglutide, a glucagon-like peptide-1 receptor agonist, on kidney function of HFD-induced obese mice, is associated with an increased expression of genes involved in cardiolipin synthesis and remodeling such as Crls and Taz , resulting in an increase of cardiolipin content [ 133 ].…”
Section: Targeting Cardiolipin To Treat Obesitymentioning
confidence: 99%